COMMUNICATIVE GRAMMAR AS ONE OF THE LANGUAGE SYSTEMS - Ruziev Khusniddin Bakhritdinovich (Web of Journals Publishing, 2024)
This article deal with communicative grammar and it’s role in teaching English language. Components and strategies used in communicative grammar teaching are given information.
Keywords: communicative grammar, contextualization, task-based learning, role-playing and simulations.